Characterization of Filmogenic/Edible Covering Based on Pectin Extracted from Cajá (Spondias mombin) Applied to Coating Green Acerolas (Malpighia emarginata) - Alves Asevedo, Estéfani; Dantas de Oliveira Júnior, Sérgio; Silvino dos Santos, Everaldo (Journal of Chemical Engineering Research Updates, 2021)
Filmogenic coatings can be used as a post-harvest strategy to extend shelf life and ensure improvements in fruit quality and safety given their perishable nature. Due to their edibility, the composition of the coverings is a determining factor for their application, and for this reason, it is interesting and desirable that the constituents come from natural sources. The objective of the present study was to develop and characterize a pectin-based film extracted from cajá peel (Spondias mombin) and verify its efficiency as an edible coating in postharvest acerolas (Malpighia emarginata). The film was characterized in terms of mechanical properties by Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM); as well as in terms of chemical properties using the analysis of structural bonds by Fourier Transformed Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD). In addition, the antimicrobial activity against two bacteria was evaluated. The analyzed film was presented as a dense membrane, with the presence of pores, fissures, and a very rough surface. The degree of esterification of pectin extract from cajá peel was 44%, and for this reason it was classified as low methocxyl (LM) pectin. The filmogenic solution presented antimicrobial activity against the bacteria Pseudomonas aeruginosa and Staphylococcus aureus. The applicability of the edible coating was tested on green acerolas, monitoring their maturation stage through analyzes such as weight loss, titratable acidity, and total soluble solids. At the end of the 7 days of storage, acerolas with the application of the coating showed 8.97% weight loss while acerolas without coating showed 9.89%; the percentage of total soluble solids was 7.68% higher for acerolas with the coating, as well as ascorbic acid content was higher for the protected fruits, indicating that the coverage favored the delay in the maturation of acerolas.